Sub-surface drip fertigation improves seed cotton yield and monetary returns - Singh, Kulvir; Singh, Prabhsimran; Singh, Manpreet; Mishra, Sudhir Kumar; Iqbal, Rashid; Al-Ashkar, Ibrahim; Habib-ur-Rahman, Muhammad; El Sabagh, Ayman (Frontiers in Plant Science, 2022)
Surface flood (SF) method is used to irrigate cotton in India which results in huge wastage of water besides leaching of nutrients. This necessitates for adopting of efficient management strategies to save scarce water without compromising yield. Therefore, a 2 yr field investigation was conducted under two climatic regimes (Faridkot and Abohar) to study the effect of sub-surface drip fertigation (SSDF) on seed cotton yield (SCY), water productivity, nitrogen use efficiency (NUE) and economic parameters in comparison with SF and surface drip fertigation (SDF).The field experiment had a total of 8 treatments arranged in a randomized complete block design. Three levels of sub-surface drip irrigation-SSDI {i.e. 60, 80 and 100% of crop evapotranspiration (ETc)} and two N fertigation levels [100% RDN (recommended dose of nitrogen i.e.112.5 kg N ha-1) and 75% RDN ] made 6 treatments, while SF (Control 1) and SDF at 80% ETc (Control 2), both with 100% of RDN served as controls. Among irrigation regimes, SSDI levels of 80% ETc and 100% ETc recorded 18.7% and 21.1% higher SCY as compared to SF. Water use efficiency (WUE) under SF was reduced by 34.2%, 40.8% and 38.2% as compared to SSDI’s of 60, 80 and 100% ETc, respectively. Among fertigation levels, NUE was higher by 19.2% under 75% over 100% RDN, but later also registered 11.9% higher SCY indicating it to be optimum for better productivity. SSDF at 80% ETc along with 112.5 kg N ha-1 recorded 26.6% better SCY and 18.5% higher NUE over SF. These findings demonstrate that application of SSDF could save irrigation water, enhance SCY and improve farmers’ returns as compared to SF. Therefore, in North-Western India, SSDF at 80% ETc along with 112.5 kg N ha-1 could be a novel water savvy concept which would be immensely helpful in enhancing cotton productivity.